Pendidikan Sebagai Human Investasi - Saleh Adri, Harli (Islamic Education Journal, 2022)
The purpose of this study is to analyze education as a human investment, the method used is library research, the results of the research are in the form of various problems faced by our nation in increasing state income. Of course, to get such high income, we have to fix various sectors in the country. One area of ??challenge is the field of education, namely how to develop an education system that is able to improve the quality of Human Resources evenly, so as to produce good results. It can be seen that in recent years the Indonesian nation has made improvements in the field of education. Education is a fundamental thing that must be passed by every individual. If you want to progress and develop then improve the quality of education. For the community there is no reason not to be educated because the government is responsible for its people to receive education, such as providing facilities and infrastructure, operational funds, as well as scholarships for the community, and so on.